Locking Compression Plate fixation of radial and tibial fractures in a young dog - Schwandt, C. S.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
A six-month-old, male Bernese Mountain Dog in which radius-ulna and tibia-fibula concomitant fractures were treated each with a 3.5 mm Locking Compression Plate (LCP) is presented. Both fractures were approached and plated medially. The tibial fracture had to be revised with a 4.5 mm intramedullary nail and a new 3.5 mm LCP at the second post-operative day because of fixation breakdown. The follow-up radiographs taken at days 14 and 53 revealed uneventful healing of both fractures. Implants were removed 53 days after surgery.
Keywords: Dog; LCP; radius; tibia